A Web-based TelePACS using an asymmetric satellite system. - Seon-Cheol Hwang
We have developed a WWW-based TelePACS that can access every permitted PACS server via the Internet. Java programming techniques were used to implement the system, which can access and retrieve medical information and images through Web browsers such as netscape without specific tools. We also have developed a consolidator that performs as a manager to connect a conventional PACS server to a Web-based TelePACS server. We have developed the asymmetric satellite data communication system (ASDCS) as a fast communication system. The ASDCS uses a receive-only satellite link for data delivery and a terrestrial network for control communication. In conclusion, we were able to develop a cost-effective and fast PACS using Web technology. Web technology expanded the scope of use for a dedicated PACS from intrahospital to public use.
Keywords: ASDCS; Internet; Java programming; PACS server; Web browser; Web browsers; Web-based TelePACS; Asymmetric satellite data communication system; Asymmetric satellite system; Data delivery; Fast communication system; Medical information; Public telemedicine systems; Receive-only satellite link; Remote image viewing systems; Teleconsultation systems; Teleeducation systems; Terrestrial network